2005
DOI: 10.1159/000085993
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Provides Neuroprotection in the Late-Gestation Fetal Sheep Brain in Response to Umbilical Cord Occlusion

Abstract: Oxygen free radicals, including the highly toxic hydroxyl radical (·OH), initiate lipid peroxidation and DNA/RNA fragmentation and damage cells. The pineal hormone melatonin is an antioxidant and powerful scavenger of ·OH. We hypothesized that maternally administered melatonin could reduce ·OH formation, lipid peroxidation, and DNA/RNA damage in the fetal brain in response to asphyxia. In 15 fetal sheep, extracellular ·OH was measured by microdialysis in white and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
126
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 132 publications
(134 citation statements)
references
References 98 publications
(57 reference statements)
6
126
2
Order By: Relevance
“…In these studies melatonin given at doses of more than 5 mg/kg, with treatment starting either before or during ischemia, showed maximum protection. In contrast, experiments in term fetal sheep did not find an effect of melatonin treatment on DNA/RNA fragmentation following umbilical cord occlusion, although the increase in hydroxyl radicals was prevented (19). However, these experiments differed from the present study with regard to several aspects; a lower melatonin dose (1 mg/kg) and shorter infusion period (2h) were used and the drug was administered to the mother rather than the fetus.…”
Section: Discussioncontrasting
confidence: 95%
“…In these studies melatonin given at doses of more than 5 mg/kg, with treatment starting either before or during ischemia, showed maximum protection. In contrast, experiments in term fetal sheep did not find an effect of melatonin treatment on DNA/RNA fragmentation following umbilical cord occlusion, although the increase in hydroxyl radicals was prevented (19). However, these experiments differed from the present study with regard to several aspects; a lower melatonin dose (1 mg/kg) and shorter infusion period (2h) were used and the drug was administered to the mother rather than the fetus.…”
Section: Discussioncontrasting
confidence: 95%
“…Therefore, not surprisingly, there is direct and indirect evidence that oxidative stress plays a central role in mediating developmental brain injury [16,19,23]. In late gestation fetal sheep, we have used umbilical cord occlusion to show that acute fetal asphyxia causes increased production of hydroxyl radical within the fetal brain, predominantly in the grey matter [24], and widespread upregulation of lipid peroxidation (4-HNE positive cells) in both the grey and white matter [25]. Our observations are supported by those of others where upregulation of free radicals and lipid peroxidation products within the brain following acute perinatal asphyxia has been shown to occur across a range of species and under varying experimental conditions [26,27,28].…”
Section: Hypoxia and The Developing Brainmentioning
confidence: 99%
“…In fetal sheep, Miller et al 11 showed that maternal prophylactic melatonin (1 mg total) given before 10-minute umbilical cord occlusion at term-equivalent was associated with reduced brain lipid peroxidation, neuronal death, microglial activation, and astrogliosis. 11,12 In preterm fetal sheep at 0.6 gestation (Term ¼ 147 days) fetal infusion of high-dose (20 mg/kg) …”
mentioning
confidence: 99%